From Cancer to Immune-Mediated Diseases and Tolerance Induction: Lessons Learned From Immune Oncology and Classical Anti-cancer Treatment - Klöß, Stephan; Dehmel, Susann; Braun, Armin; Parnham, Michael J.; Köhl, Ulrike; Schiffmann, Susanne (Frontiers in Immunology, 2020)
Success in cancer treatment over the last four decades has ranged from improvements in classical drug therapy to immune oncology. Anti-cancer drugs have also often proven beneficial for the treatment of inflammatory and autoimmune diseases. In this review, we report on challenging examples that bridge between treatment of cancer and immune-mediated diseases, addressing mechanisms and experimental models as well as clinical investigations. Patient-derived tumor xenograft (PDX) (humanized) mouse models represent useful tools for preclinical evaluation of new therapies and biomarker identification. However, new developments using human ex vivo approaches modelling cancer, for example in microfluidic human organs-on-chips, promise to identify key molecular, cellular and immunological features of human cancer progression in a fully human setting. Classical drugs which bridge the gap, for instance, include cytotoxic drugs, proteasome inhibitors, PI3K/mTOR inhibitors and metabolic inhibitors. Biologicals developed for cancer therapy have also shown efficacy in the treatment of autoimmune diseases. In immune oncology, redirected chimeric antigen receptor (CAR) T cells have achieved spectacular remissions in refractory B cell leukemia and lymphoma and are currently under development for tolerance induction using cell-based therapies such as CAR Tregs or NK cells. Finally, a brief outline will be given of the lessons learned from bridging cancer and autoimmune diseases as well as tolerance induction.